Complete response to PD-1 blockade following EBV-specific T-cell therapy in metastatic nasopharyngeal carcinoma - Corey Smith; Margaret McGrath; Michelle A. Neller; Katherine K. Matthews; Pauline Crooks; Laetitia Le Texier; Benedict Panizza; Sandro Porceddu; Rajiv Khanna (npj Precision Oncology, 2021)
Abstract Nasopharyngeal carcinoma (NPC) is an Epstein–Barr virus (EBV)-associated heterogeneous disease and is characterized by peritumoral immune infiltrate. Adoptive T-cell therapy (ACT) has emerged as a potential therapeutic strategy for NPC. However, the tumor microenvironment remains a major roadblock for the successful implementation of ACT in clinical settings. Expression of checkpoint molecules by malignant cells can inhibit the effector function of adoptively transferred EBV-specific T cells. Here we present a novel case report of a patient with metastatic NPC who was successfully treated with a combination of EBV-specific ACT and programmed cell death-1 blockade therapy. Following combination immunotherapy, the patient showed complete resolution of metastatic disease with no evidence of disease relapse for 22 months. Follow-up immunological analysis revealed dramatic restructuring of the global T-cell repertoire that was coincident with the clinical response. This case report provides an important platform for translating these findings to a larger cohort of NPC patients.